Network coding for reliable wireless sensor networks - al-hawri, eman (2020)
Wireless sensor networks are used in many applications and are now a key element in the increasingly growing Internet of Things. These networks are composed of small nodes including wireless communication modules, and in most of the cases are able to autonomously con gure themselves into networks, to ensure sensed data delivery. As more and more sensor nodes and networks join the Internet of Things, collaboration between geographically distributed systems are expected. Peer to peer overlay networks can assist in the federation of these systems, for them to collaborate. Since participating peers/proxies contribute to storage and processing, there is no burden on speci c servers and bandwidth bottlenecks are avoided. Network coding can be used to improve the performance of wireless sensor networks. The idea is for data from multiple links to be combined at intermediate encoding nodes, before further transmission. This technique proved to have a lot of potential in a wide range of applications. In the particular case of sensor networks, network coding based protocols and algorithms try to achieve a balance between low packet error rate and energy consumption. For network coding based constrained networks to be federated using peer to peer overlays, it is necessary to enable the storage of encoding vectors and coded data by such distributed storage systems. Packets can arrive to the overlay through any gateway/proxy (peers in the overlay), and lost packets can be recovered by the overlay (or client) using original and coded data that has been stored. The decoding process requires a decoding service at the overlay network. Such architecture, which is the focus of this thesis, will allow constrained networks to reduce packet error rate in an energy e cient way, while bene ting from an e ective distributed storage solution for their federation. This will serve as a basis for the proposal of mathematical models and algorithms that determine the most e ective routing trees, for packet forwarding toward sink/gateway nodes, and best amount and placement of encoding nodes.